Punishment and Economic Inequality: Estimating Short-Term and Long-Term Equilibrium Relationships - Kim, Dae Young (Criminal justice policy review, 2017)
During the post-World War II (WWII) period, U.S. prison populations and economic inequality have historically shared a common trend. Both indexes were low and fairly stable until the early 1970s, but afterward, they rose significantly. In the context of the prison boom and high economic inequality, such a meaningful coincidence that both variables follow the same trend calls for the present study examining their historical long-term relationship. With annual national data from 1950-2010, this study uses time-series regression techniques within a co-integration and error-correction framework. Although estimated results are sensitive to the model specification used in parameter estimation, there are in general both short-term and long-term equilibrium relationships between the two variables. Finally, this study concludes with a discussion of implications for policy development and future research.